2012
DOI: 10.1007/s15010-012-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-Escherichia coli community-acquired bacteriuria

Abstract: For adult outpatients presenting with CA-Bu, five independent factors suggesting the involvement of uropathogens other than E. coli were identified. These should be taken into consideration when empiric antibiotic treatment is prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Considering the dominant isolates ( Fig. 2A), the overlapping species found commonly in both patients and controls included those known to be associated with acute UTIs, including E. coli (implicated in up to 80% of acute UTI episodes [33]), Enterococcus spp., Staphylococcus spp., and Streptococcus spp. In contrast, a number of bacteria were found most frequently only in patients, such as Proteus spp.…”
Section: Spectrum Of Lutsmentioning
confidence: 99%
“…Considering the dominant isolates ( Fig. 2A), the overlapping species found commonly in both patients and controls included those known to be associated with acute UTIs, including E. coli (implicated in up to 80% of acute UTI episodes [33]), Enterococcus spp., Staphylococcus spp., and Streptococcus spp. In contrast, a number of bacteria were found most frequently only in patients, such as Proteus spp.…”
Section: Spectrum Of Lutsmentioning
confidence: 99%
“…Amna et al. also showed that the proportion of E. coli as an uropathogen in community‐acquired bacteriuria was 58.6%, with 9.5% of Enterococcus spp in 2009. The proportion of E. coli as an uropathogen was higher than those in previous studies , but similar to what was reported in recent studies conducted in 2009 (73.0–74.0%) .…”
Section: Discussionmentioning
confidence: 97%
“…Abnormalities in the urinary tract, male gender, younger age and previous antibiotic consumption in the past month have been reported as risk factors for non‐ E. coli community‐onset UTI in children . One study showed that presence of foreign body in the urinary tract, nitrite urine test negative, male gender, recurrent UTI and normal erythrocyte count in urine test were independent risk factors for non‐ E. coli in adult community‐onset bacteriuria . While the epidemiological features of uropathogenic E. coli have been extensively studied, comparatively little is known about the association between uropathogens other than E. coli and the risk factors for their acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Again, symptoms are important in the diagnosis of UTI, and acute dysuria (<1 week duration) has been reported to be the most predictive symptom. 14 The presence of virulent or resistant organisms should prompt further evaluation. 8 When symptoms are unclear, antibiotic treatment can be delayed until further evaluation is completed, including a urine culture.…”
Section: Casementioning
confidence: 99%
“…14 Resistance of E coli to fluoroquinolones is increasing and is highest in patients older than 65 years. What is the best antibiotic for acute treatment?…”
Section: Casementioning
confidence: 99%